2017
DOI: 10.1007/jhep02(2017)042
|View full text |Cite
|
Sign up to set email alerts
|

Chiral phase transition of QCD with N f = 2 + 1 flavors from holography

Abstract: Chiral phase transition for three-flavor N f = 2 + 1 QCD with m u = m d = m s is investigated in a modified soft-wall holographic QCD model. Solving temperature dependent chiral condensates from equations of motion of the modified soft-wall model, we extract the quark mass dependence of the order of chiral phase transition in the case of N f = 2 + 1, and the result is in agreement with the "Columbia Plot", which is summarized from lattice simulations and other non-perturbative methods. First order phase transi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 110 publications
(153 reference statements)
1
30
0
Order By: Relevance
“…In this case, one can check S a , π b , η vanish if there are no extra source of the corresponding operator. The phase structure in this situation has been studied in [52][53][54][55][56][57][58][59][60][61][62][63][64] . In this work, since we would like to discuss the effects of isospin chemical potential on phase transition, we have to take non-vanishing V M , A M .…”
Section: Soft Wall Model With Finite Isospin Chemical Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, one can check S a , π b , η vanish if there are no extra source of the corresponding operator. The phase structure in this situation has been studied in [52][53][54][55][56][57][58][59][60][61][62][63][64] . In this work, since we would like to discuss the effects of isospin chemical potential on phase transition, we have to take non-vanishing V M , A M .…”
Section: Soft Wall Model With Finite Isospin Chemical Potentialmentioning
confidence: 99%
“…In [55,57,58,63], we have shown that the qualitative properties of chiral phase transition could be well described when the dilaton profile takes the following form…”
Section: Soft Wall Model With Finite Isospin Chemical Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The deconfinement phase transition has been widely discussed with the expectation value of Polyakov loop as the order parameter of deconfinement phase transition. However, till recently, the dynamical spontaneous chiral symmetry breaking and chiral phase transition have been realized in soft-wall holographic QCD model [99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] with the chiral condensate as the order parameter.…”
Section: Introductionmentioning
confidence: 99%
“…By considering heavy quarks we further our exploration of the QCD phase diagram, specifically the Columbia Plot which characterizes the phase transition as a function of m u,d and m s [15]. We explore a 3-flavor symmetric model (m l = m u,d = m s ) and a 2+1-flavor model (m l = m u,d = m s ), extending the work of [16] to finite quark chemical potential.…”
Section: Introductionmentioning
confidence: 99%